A comparative study of rainfall and cotton crop under crop-weather scheme at Akola and Nagpur - SREENIVASAN , P.S.; BANERJEE, J.R. (MAUSAM, 1958)
A comparative study of rainfall and cotton crop under crop-weather scheme at Akola and Nagpur